EFFECTIVENESS OF USING THE TUBERCULOSIS INFORMATION SYSTEM (SITB) APPLICATION AND ITS IMPACT ON TB CASE DATA AT THE MERAUKE HEALTH OFFICE (Case Study at The Merauke Health Office) - Tumanggor, Eduardus Parulian; Pramudho, Kodrat; Muskita, Nevile R. (Transpublika Publisher, 2024)
This study aims to analyze the problem of utilizing the Tuberculosis Information System (SITB) application and its impact on tuberculosis (TB) case data in the working area of the Merauke Health Office. Using a qualitative approach, the main objectives of this research are to measure the effectiveness of the SITB application in recording and reporting TB cases, identify the challenges faced by health workers in using this application, analyze the impact of using the SITB application on the accuracy of TB case data, and evaluate the effect of timely data input on the quality of TB case reports submitted through SITB. Data were collected through in-depth interviews with the P2P division of the Merauke Health Office, heads of health centers, TB nurses, laboratory analysts, and TB patients, as well as direct observation of the application’s use in the field. The results of this study are expected to provide valuable insights for the Merauke Health Office in improving the use of the SITB application, thereby enhancing the accuracy and quality of reported TB case data, and to offer recommendations to overcome the challenges encountered in the application’s use.